Hubungan Antara Intensitas Olahraga dengan Kualitas Tidur pada Mahasiswa/I Fakultas Kedokteran Universitas Tarumanagara Angkatan 2021-2022 - Muhammad Naufal Razaan; Susy Olivia Lontoh (Malahayati Nursing Journal, 2024)
ABSTRACT The quality of sleep in medical students is susceptible to decreasing due to the shorter quantity of sleep time. The busy study schedule of students, especially medical faculties, exposes them to an increased risk of various sleep problems and their consequences. Poor sleep quality is associated with anxiety and depression, and can interfere with learning and academic achievement. Sleep quality can be improved one way by doing physical activity. The purpose of this research is to determine the relationship between exercise intensity and sleep quality in Tarumanagara University medical students class 2021 -2022. This type of research uses a cross-sectional design and analytical observational study with total of 100 students. The research was conducted at Tarumanagara University in January 2024 – June 2024 and was carried out by distributing a google form. Incorporation criteria of this research are students from the Faculty of Medicine Tarumanagara University class 2021-2022 who were in good health and willing to be respondents.The results showed that there is a significant relationship between exercise intensity and sleep quality in students from the Faculty of Medicine, Tarumanagara University class of 2021-2022 with p value = 0,024 (p0,05). This shows that students' sleep quality can be improved with physical activity. Keywords: Exercise intensity, Sleep Quality, Exercise, Sleep  ABSTRAK Kualitas tidur pada mahasiswa kedokteran rentan menurun akibat kuantitas waktu tidur yang lebih singkat. Padatnya jadwal belajar mahasiswa, khususnya fakultas kedokteran, membuat mereka rentan terhadap peningkatan risiko berbagai masalah tidur dan dampaknya. Kualitas tidur yang buruk dikaitkan dengan kecemasan dan depresi, serta dapat mengganggu pembelajaran dan prestasi akademik. Salah satu cara untuk meningkatkan kualitas tidur adalah dengan meningkatkan aktivitas fisik. Tujuan penelitian ini adalah untuk mengetahui hubungan intensitas olahraga dengan kualitas tidur pada mahasiswa Kedokteran Universitas Tarumanagara angkatan 2021 -2022. Jenis penelitian ini menggunakan desain cross-sectional dan studi observasional analitik dengan jumlah peserta didik sebanyak 100 orang. Penelitian dilakukan di Universitas Tarumanagara pada bulan Januari 2024 – Juni 2024 dan dilakukan dengan menyebarkan google form. Kriteria inklusi penelitian ini adalah mahasiswa Fakultas Kedokteran Universitas Tarumanagara angkatan 2021-2022 yang dalam keadaan sehat dan bersedia menjadi responden. Hasil penelitian menunjukkan bahwa terdapat hubungan yang signifikan antara intensitas olahraga dengan kualitas tidur pada mahasiswa Fakultas Kedokteran Universitas Tarumanagara angkatan 2021-2022 dengan p value = 0,024 (p0,05). Hal ini menunjukkan bahwa kualitas tidur mahasiswa/i dapat ditingkatkan dengan aktivitas fisik. Kata Kunci: Intensitas Olahraga, Kualitas Tidur, Olahraga,Tidur